Interaction Effects of the Leu162Val PPARα and Pro12Ala PPARγ2 Gene Variants with Renal Function in Metabolic Syndrome Population - Sarraj Mohamed Youssef; Najah Mohamed; Slimani Afef; Ben Hamda Khaldoun; Neffati Fadoua; Najjar Mohamed Fadhel; Slimane Mohamed Naceur (PPAR Research)
Leu162Val PPARα and Pro12Ala PPARγ2 were investigated for their individual and their interactive impact on MS and renal functionality (RF). 522 subjects were investigated for biochemical and anthropometric measurements. The diagnosis of MS was based on the IDF definition (2009). The HOMA 2 was used to determine HOMA-β, HOMA-S and HOMA-IR from FPG and FPI concentrations. RF was assessed by estimating the GFR. PCR-RFLP was performed for DNA genotyping. Allele frequencies were 0.845 for Pro and 0.155 for Ala, and were 0.915 for Leu and 0.085 for Val. We showed that carriers of the PPARα Val 162 allele had lower urea, UA and higher GFR compared to those homozygous for the Leu162 allele. Subjects carried by PPARγ2Ala allele had similar results. They also had reduced FPG, FPI and HOMA-IR, and elevated HOMA-β and HOMA-S compared to those homozygous for the Pro allele. Subjects were divided into 4 groups according to the combinations of genetic alleles of the 2 polymorphisms. Subjects carrying the Leu/Val with an Ala allele had lower FPG, PPI, HOMA-IR, urea, UA levels, higher HOMA-β, HOMA-S and GFR than different genotype combinations. Leu162Val PPARα and Pro12Ala PPARγ2 can interact with each other to modulate glucose and insulin homeostasis and expand their association with overall better RF.